Positive and negative affect during a pandemic: Mediating role of emotional regulation strategies - Ahmet Kara; Ayşe Gök (Journal of Pedagogical Research, 2020)
The purpose of the current study is to determine the mediator role of emotional regulation strategies in the relationship between positive affect and negative affect experienced by individuals during the COVID-19 pandemic. A total of 436 individuals witnessing and experiencing the process of the COVID-19 pandemic in Turkey participated in the current study and 310 (71.1%) of the participants are females and 126 (28.9%) are males. The data of the current study were collected by using the Positive - Negative Affect Scale and Emotional Regulation Questionnaire. The path analysis technique was used in the analysis of the data. In order to test the significance of indirect effects, bootstrapping analysis was used by generating 1000 samples. According to the findings of the study, one unit increase in negative affect decreases individuals' use of emotional regulation strategies by 0.13 (t= -.2.829; p<.01 ). On the other hand, one unit increase in emotional regulation strategies increases individuals' positive affect by 0.43 (t = 9.848; p<.01 ). In addition, the full mediator role of emotional regulation strategies in the relationship between negative affect and positive affect has been proven. It is thought that the findings obtained as a result of the research can be a guide for mental health professionals and future research.